Brief communication: Enabling open cryosphere research with Ghub - J. P. Tulenko; J. P. Tulenko; S. A. Goliber; R. Jones-Ivey; J. Quinn; A. Patra; K. Poinar; K. Poinar; S. Nowicki; S. Nowicki; B. M. Csatho; J. P. Briner (The Cryosphere, 2025)
We report on the infrastructure and scientific progress of the Ghub project, a scientific gateway providing an open-access online platform for cryosphere researchers to publish and share tools and datasets. Ghub is designed to reduce bottlenecks and accelerate progress in cryosphere sciences. Open-access science lowers barriers, encourages collaboration, and expands the network of participants in research, which is particularly important for cryosphere science given the major impact of climate change on the world's glaciers and ice sheets, whose demise contributes to sea level rise. We conclude with a brief synopsis of what the future holds for the Ghub project.